Respiratory failure and mechanical ventilation in severe bronchiolitis. Issue 10 (October 1989) - Lebel, M H; Gauthier, M; Lacroix, J; Rousseau, E; Buithieu, M
Abstract : A retrospective review of children who needed mechanical ventilation for severe bronchiolitis identified 62 cases over a 10 year period. The mean age at initiation of ventilation was 73 days (range: 14-201). Compared with a group of 150 children in hospital for bronchiolitis but not transferred to the intensive care unit, these 62 cases were significantly younger (73.0 compared with 166.3 days), and smaller (4.5 compared with 6.8 kg), and significantly more had been born prematurely (40% compared with 16%). Taken independently, age, weight, and prematurity were significantly associated with the need for artificial ventilation, weight being the most important factor. Using stepwise logistic regression, prematurity in itself added to the quality of the prediction but age did not. The mean duration of mechanical ventilation was 105 hours (range 2-381). Duration of ventilation was significantly longer in children with a low gestational age at birth and a positive familial history of atopy. There were no deaths, and no patient developed pneumothorax or pneumomediastinum. Mechanical ventilation is well tolerated and safe in acute bronchiolitis.